THE EFFECT OF JIGSAW COOPERATIVE LEARNING MODEL WITH SCRAPBOOK ON STUDENTS MOTIVATION AND LEARNING OUTCOMES - Miftahul Ulum; Ruri Nurul Aeni Wulandari (Jurnal Scientia, 2023)
This study aims to describe the effect of the jigsaw-assisted cooperative learning model of the scrapbook-assisted type on the motivation and learning outcomes of students at SMK Krian 2 Sidoarjo. This research method is a Quasi Experimental Design with the form of a Nonequivalent Control Group Design experiment. The research sample was taken by purposive sampling technique. The research was conducted in class XI MPLB 1 as the experimental class and class XI MPLB 3 as the control class. Data analysis techniques in this study used prerequisite tests in the form of normality and homogeneity tests and hypothesis testing using the t-test (t-test). The results of this study indicate that the application of the jigsaw-assisted cooperative learning model with the help of scrapbooks has an effect on learning motivation as indicated by an increase in students' motivation scores before and after treatment. In addition, the results of the study also showed that the jigsaw-assisted cooperative learning model with the help of scrapbooks had an effect on student learning outcomes which were known to increase the learning outcomes of the experimental class which were higher than the control class. Keywords: Learning Model, Jigsaw, Scrapbook, Motivation, Learning Outcomes